Data mining tool for academic data exploitation: publication report on engineering students profiles - Barbu, Marian (2019)
This report summarizes the findings of the project SPEET. It relies on the initial document generated as Intellectual Output #1 and the results obtained by application of the IT tools developed in Intellectual Output #2, and Intellectual Output #3 to the academic data provided by the partner institutions. The main objectives of applying analytic techniques to evaluate the academic data sources can be categorized as follows: Improve Student Results; Create Mass-customized Programs; Improve the Learning Experience in Real-time; Reduce Dropouts and Increase Results.